2015
DOI: 10.1186/s12876-015-0320-4
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of sofosbuvir-based treatments for chronic hepatitis C in the US

Abstract: BackgroundThe standard care of treatment of interferon plus ribavirin (plus protease inhibitor for genotype 1) are effective in 50 % to 70 % of patients with CHC. Several new treatments including Harvoni, Olysio + Sovaldi, Viekira Pak, Sofosbuvir-based regimens characterized with potent inhibitors have been approved by the Food and Drug Administration (FDA) providing more options for CHC patients. Trials have shown that the new treatments increased the rate to 80 % to 95 %, though with a substantial increase i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 24 publications
1
43
0
2
Order By: Relevance
“…[40][41][42][43] Most studies concluded that it is costeffective to treat genotype 1 with interferon-free direct-acting antiviral agents compared with pegylated interferon-ribavirin-based direct-acting antiviral agents. More recently, additional studies have reported incremental cost-effectiveness for other genotypes.…”
Section: Discussionmentioning
confidence: 99%
“…[40][41][42][43] Most studies concluded that it is costeffective to treat genotype 1 with interferon-free direct-acting antiviral agents compared with pegylated interferon-ribavirin-based direct-acting antiviral agents. More recently, additional studies have reported incremental cost-effectiveness for other genotypes.…”
Section: Discussionmentioning
confidence: 99%
“…1. Fourteen studies were then included in the review, all of them published in English [16][17][18][19][20][21][22][23][24][25][26][27][28][29].…”
Section: Systematic Literature Searchmentioning
confidence: 99%
“…In the 14 studies, which were published between 2013 and 2015, health economic evaluations for seven different countries were conducted: France [21], Germany [19], Italy [17,25], Spain [28], Switzerland [26], the UK [18] and the USA [16, 20, 22-24, 27, 29]. In all studies, the cost-effectiveness of sofosbuvir-based treatment was assessed from the perspective of the respective payer, though Zhang et al [29] did not state the perspective of their analysis. In four studies, the authors stated that a societal perspective was applied [20,21,23,24]; none of them, however, considered costs other than direct medical costs.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations